Infective Endocarditis Presented as a Right Atrium Mass in a Patient with Ulcerative Colitis - Ali Asghar Moeinipour; Hamid Hoseinikhah; Mohamad Ali Kiani; Naser Tayyebi Meibodi; Mohammad Hassan Aelami; Ali Reza Sepehri Shamloo; Shahram Amini (Case Reports in Cardiology)
Involvement of the heart is infrequently seen in irritable bowel syndrome (IBD). We present a case of severe acute infective endocarditis diagnosed as ulcerative colitis in further workup.